International Business - K Ashwathappa (Chennai, 2020)
This book covers the entire gamut of international business by exploring the theoretical foundations of the subject and interspersing the text with cases. It provides the latest developments in the subject with an application-based approach and a wide variety of pedagogical features. This book would not only be of immense help to management students but working professionals would also find it quite useful.
English
Keywords: International Business; Management